2012
DOI: 10.5194/acpd-12-3213-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ice nucleation efficiency of clay minerals in the immersion mode

Abstract: Emulsion and bulk freezing experiments were performed to investigate immersion ice nucleation on clay minerals in pure water, using various kaolinites, montmorillonites, illites as well as natural dust from the Hoggar Mountains in the Saharan region. DSC (differential scanning calorimeter) measurements were performed on the kaolinites KGa-1b and KGa-2 from the Clay Mineral Society and kaolinite from Sigma-Aldrich; the montmorillonites SWy-2 and STx-1b from the Clay Mineral Society and the acid treated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 81 publications
2
43
1
Order By: Relevance
“…Many laboratory studies and observations have shown that heterogeneous freezing occurs at higher temperatures (e.g., DeMott et al, 2003;McFarquhar et al, 2007;Chen et al, 2008;Niemand et al, 2012;Pinti et al, 2012). However, for IN freezing at these higher temperatures a consistent set of parameters for all five schemes as derived for kaolinite is not available.…”
Section: Model Studies At Higher Temperatures (T1 and T2)mentioning
confidence: 99%
“…Many laboratory studies and observations have shown that heterogeneous freezing occurs at higher temperatures (e.g., DeMott et al, 2003;McFarquhar et al, 2007;Chen et al, 2008;Niemand et al, 2012;Pinti et al, 2012). However, for IN freezing at these higher temperatures a consistent set of parameters for all five schemes as derived for kaolinite is not available.…”
Section: Model Studies At Higher Temperatures (T1 and T2)mentioning
confidence: 99%
“…Kaolinite is found to be efficient in the immersion mode using the cold stage method [55,56]. K-feldspars and quartz were found to be the two most efficient immersion INPs in mineral dust even though they were found in low weight percentages in samples [29].…”
Section: Immersion-mode Ice Nucleation Activitymentioning
confidence: 99%
“…In more recent experiments, improvements could be achieved as the particle surface area was determined and taken into account for the interpretation of the immersion freezing results (Connolly et al 2009;Niedermeier et al 2010;Sullivan et al 2010;Niedermeier et al 2011b;Augustin-Bauditz et al 2014;Zolles et al 2015). Other experiments examined the immersion freezing of droplets with varying particle sizes or particle loads: Archuleta et al (2005), Marcolli et al (2007), Welti et al (2009), Lüönd et al (2010), Welti et al (2012), and Pinti et al (2012) reported an increasing freezing probability with increased available particle surface area. In other words, the dependence of immersion freezing on the particle surface area was shown on a qualitative basis.…”
Section: Introductionmentioning
confidence: 99%